Iowa RBA, October 25-30, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Three emails of Iowa RBA updates for October 25, 27, and 30, 1999. Highlights of the updates include sightings of an American Tree Sparrow, Common Goldeneye, Common Redpoll, and a Black-headed Gull. Epson - sheet feed/flatbed